Is there a nexus between social entrepreneurship and the employability of graduates? - Bulelwa Mandyoli; Chux Gervase Iwu; Zinzi Nxopo (Foundations of Management, 2017)
Social entrepreneurs have, in several ways, been regarded as engines of intense socioeconomic development. They are also famous for intervening with projects for society's problems that are often either inadvertently ignored or inadequately managed by mainstream society. The issue of graduate employability has gained increased tension around the world especially in emerging markets such as South Africa. Currently, suggestions are that considering the avowed contribution of social entrepreneurs, it may be worthwhile to start examining how they can assist with graduate employability in South Africa. This paper, therefore, takes an exploratory yet focused scrutiny of the social entrepreneurship ecosystem to find out the likelihood of social entrepreneurs participating in programs that prepare students for the workplace, thereby reducing graduate unemployability. This is a conceptual paper that has benefitted from an extensive review of literature. Conclusions are drawn therefrom to suggest that opportunities exist for social entrepreneurs to provide practical, project-based learning opportunities for college and university students so that by the time they graduate, they have attained reasonable work-readiness levels that stand them in good stead for employment. While the authors propose an intensive empirical study of the subject matter, we are equally positive that this paper may be used to advance the current platforms of engagement of the role of social entrepreneurs or grow innovative methods that provide graduates with a better chance to be successful in the working environment. In short, this paper calls for sustained discussions on how social entrepreneurs can improve graduate employability.
Keywords: 650; socioeconomic development; social entrepreneurs; enterprise education; South Africa; graduate unemployment; graduate attributes; social enterprise; References